Multipotent progenitors with distinct origins, clonal lineage fates, transcriptomes, and surface markers yield two hematopoietic trees - Fuwei Shang; Tamar Nizharadze; Robin Thiele; Branko Cirovic; Larissa Frank; Katrin Busch; Weike Pei; Thorsten B. Feyerabend; Thomas Höfer; Xi Wang; Hans-Reimer Rodewald (Proceedings of the National Academy of Sciences, 2025)
Multipotent progenitors (MPP) are the quantitative source of native hematopoiesis that have been thought to be replenished slowly by hematopoietic stem cells (HSC). However, recent fate mapping studies have revealed two developmentally distinct populations of MPP, HSC-derived MPP (hMPP), and HSC-independent, embryonic MPP (eMPP). These data raise fundamental questions on the distinctions and functions of these progenitors. Here, we mapped the clonal dynamics of the two independent MPP systems, using in situ barcoding, and barcode linkage (hMPP), or disconnect (eMPP), with HSC. The cumulative output of eMPP to hematopoiesis was 35%, and their output was enriched for lymphoid fates. Conversely, hMPP output was enriched for myeloid-restricted fates. Distinguishing HSC from eMPP outputs revealed that only ~15% of adult HSC clones underwent multilineage differentiation (lymphoid, myeloid, and erythroid). To prospectively identify eMPP, we developed PolySMART for joint profiling of PolyloxExpress RNA barcodes, surface markers, and transcriptomes, and we found that the plasma cell marker CD138 enriches for eMPP. CD138 + MPP are primed for self-renewal and toward lymphoid fate, and become largely but not completely replaced by CD138 − MPP over time, which may contribute to the loss of lymphoid output with age. Taken together, adult hematopoiesis consists of two distinct lineage trees. The source of the “eMPP tree” substantially contributes to hematopoiesis before it declines, while the HSC-hMPP tree supplies hematopoiesis life-long. Our molecular determinants distinguishing the two MPP systems may open avenues to further explore these unexpected layers of hematopoiesis.